Problems In Implementing The Independent Curriculum In English Subjects In Kubu Raya - Faizal Daeng Saputra; Alvina Yolanda; Dewi Ismu Purwaningsih (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research used a qualitative approach that discusses problems that occur in SMPN 04 Rasau Jaya and Mts Al-Huda Pematang Tujuh using an independent curriculum. The independent curriculum is a new curriculum that is implemented as a refinement of the previous curriculum, namely the 2013 curriculum. In its application to learning, the independent curriculum has been developed into a more variable curriculum but still focuses on basic materials, character development and competence in students. As in his review, the independent curriculum has a goal as a recovery to the learning crisis that is getting worse due to the pandemic, besides that it also aims to provide freedom to institutions and teachers to develop and manage curricula and learning that are tailored to the characteristics of educational units and students. This study took several respondents consisting of school principals, related teachers and several students who were thought capable and understood related to this research. In data collection, interviews, field observations and documentation are used. The results of this study stated that there were three problems that occurred in the implementation of the independent curriculum and efforts made to overcome these problems. The three problems are the difficulty of changing the old mindset or habits in the application of learning, the application of differentiated learning that is less than optimal, and the number of different learning tools in one institution.